2012
DOI: 10.1186/1472-6882-12-116
|View full text |Cite
|
Sign up to set email alerts
|

Arctium lappa ameliorates endothelial dysfunction in rats fed with high fat/cholesterol diets

Abstract: BackgroundArctium lappa L. (Asteraceae), burdock, is a medicinal plant that is popularly used for treating hypertension, gout, hepatitis, and other inflammatory disorders. This study was performed to test the effect of ethanol extract of Arctium lappa L. (EAL) seeds on vascular reactivity and inflammatory factors in rats fed a high fat/cholesterol diet (HFCD).MethodEAL-I (100 mg·kg−1/day), EAL-II (200 mg·kg−1/day), and fluvastatin (3 mg·kg−1/day) groups initially received HFCD alone for 8 weeks, with EAL suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…We also excluded one study because it compared different doses of yoga (Saper 2013), and one study because it compared different yoga techniques (Haldavnekar 2014). Finally, we excluded six references because they were not original study reports (Graves 2004; Borg-Olivier 2005; Anon 2006; Horng 2006; Anon 2009; Selfridge 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We also excluded one study because it compared different doses of yoga (Saper 2013), and one study because it compared different yoga techniques (Haldavnekar 2014). Finally, we excluded six references because they were not original study reports (Graves 2004; Borg-Olivier 2005; Anon 2006; Horng 2006; Anon 2009; Selfridge 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Burdock (Arctium lappa L.), a biennial plant belonging to the Compositae family, has been cultivated in Eastern Asian countries, particularly in Taiwan, China and Japan for use in cooking and in folk medicine as a diuretic, antipyretic and blood purifying agent (8-10). Pharmacologically, burdock has been identified to possess hepatoprotective (11,12), desmutagenic (13), antibacterial (14,15), gastroprotective (16,17), anti-hypoglycemic (18,19), anti-hypolipidemic (20), anti-inflammatory (21), antifatigue (22), antioxidant (10,21,23), body weight management (24) and aphrodisiac (25) activities. Therefore, burdock-containing health drinks and foods are widely consumed in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic treatment with EAL also suppressed increases in matrix metalloproteinase-2 expression. These results suggested that EAL can inhibit HFCD-induced vascular inflammation in the rat model [77].…”
Section: Vasodilatory and Vasculoprotective Activitymentioning
confidence: 66%